Breeding Biology of Feather-Back Notopterous notopterus from Keenjhar Lake, District Thatta, Sindh, Pakistan - Chandio, M.H.; Narejo, N.T.; Jalbani, S.; Khan, P. (Pakistan Journal of Nutrition, 2016)
Breeding biology was elucidated in terms of ova diameter, gonadosomatic index (GSI %) and fecundity of Notopterus notopterus from Keenjhar Lake, district Thatta, Sindh, Pakistan during May to September 2014. It was observed that the size of ova starts increasing from 1.0-2.82 mm during the study period and found highest (2.82) in July. The GSI % values were also found to increase from 0.1 to 1.83 and 3.72 to 7.92 for male and female, respectively. The estimation of fecundity in the present course of investigation was based on 12 graved fish. The fecundity of N. notopterus was ranged from 105-1500 eggs. The highest (1500 eggs) was recorded from the fish of 30.5 cm and 313.8 g and lowest (105 eggs) was recorded from the fish of 18.5 cm and 66.5 g in length and weight, respectively. It was concluded that the experimental fish N. notopterous was found to be low fecund fish as compare to carps due to bigger size of eggs and single lobed ovary. Fecundity was plotted against different body parameters like total length, body weight and gonad weight and found that it bears strong relationship with the total length.